Coastal Water Quality Index (CWQI) Assessment of Youtefa Bay, Jayapura: Status and Management Implications - Suhartawan, Bambang; Daawia, Daawia (Journal of Health and Nutrition Research, 2025)
This research aims to assess the water quality status of Youtefa Bay in Jayapura City using the Coastal Water Quality Index (CWQI) method. Youtefa Bay is an important ecological area with mangrove, seagrass, and coral reef ecosystems that currently face anthropogenic pressures. A quantitative approach with descriptive analytical design was conducted through sampling at 12 stations during the dry season (June) and rainy season (November) 2024. Parameters measured included physical aspects (temperature, transparency, turbidity, TSS, salinity), chemical aspects (pH, DO, BOD, COD, nitrate, phosphate, ammonia, heavy metals), and biological aspects (chlorophyll-a, coliform, E. coli, phytoplankton). Results showed that the overall CWQI value for Youtefa Bay was 71.24 (classified as "Fair"). Significant spatial variation was observed with residential zones having the lowest CWQI (58.75, "Marginal"), port zones (62.41, "Marginal"), mangrove zones (68.35, "Fair"), and the central bay area having the highest value (83.42, "Good"). Principal Component Analysis identified eutrophication-related parameters (turbidity, TSS, BOD, nitrate, phosphate) as the main determinants of water quality, contributing 43.65% of the total variance. Temporal analysis showed lower water quality during the rainy season (CWQI=62.8) compared to the dry season (CWQI=74.5). Strong correlations were found between anthropogenic activities and water quality, with population density negatively correlated (r=-0.854) and mangrove cover positively correlated (r=0.765). Sustainable management strategies were formulated, prioritizing domestic waste management, mangrove rehabilitation, development of integrated monitoring systems, community empowerment, and strengthening stakeholder coordination. This research provides a scientific basis for effective bay management